Bioresource-derived polymer composites for energy storage applications: Brief review. Issue 5 (October 2021) - Anthony, Leonard Sean; Vasudevan, Mugashini; Perumal, Veeradasan; Ovinis, Mark; Raja, Pandian Bothi; Edison, Thomas Nesakumar Jebakumar Immanuel
Abstract: Biopolymers derived from bioresources have gained significant interest over the past decade owing to the industrial shift toward more environmentally friendly materials and devices. These organic materials are highly favored as an important alternative to conventional materials because of their lightweight nature and high strength and stiffness. Hence, the use of biopolymers is being extended to several fields, including packaging, agriculture, automotive, medical, and electronics. Electrochemical energy storage devices, such as batteries and supercapacitors, can be fabricated via custom biopolymer production methods. They are either chemically produced from bioresources or are genetically modified organisms. Although the prospective applications of biopolymers are limited, they still need to be used in combination with other materials in composites. This helps to improve their inherent physical characteristics in addition to the electrochemical performance of the biologically active molecules. The current review provides a detailed introduction to several biopolymer production methods and a comprehensive account of recent advances, especially the use of different additives in bioresource-derived polymer composites for both batteries and supercapacitors. Graphical Abstract: ga1 Highlights: Supercapacitors and battery development is a rapid growing research field. Bio-resource polymers well utilized for fabricating supercapacitors/batteries. Literature strongly evident their performance/promising alternate for electrodes. Bio-polymer composites for supercapacitors and battery application were reviewed.